The Cauca Indigenous Guard: a form of alter-geopolitics - Benítez Loaiza , José David (El Outsider: Journal of International Relations and Political Science, 2021)
For decades, the Republic of Colombia has faced an armed conflict where different guerrilla and paramilitary groups, drug cartels, and the State itself converge. In this scenario, and despite efforts to achieve peace in recent years, there are still territories such as Cauca, where violence is latent. Given this, indigenous peoples have adopted different forms of resistance to the armed conflict per se and its derived consequences. This article analyzes these terror scenarios and the implementation of the “indigenous guard” of the indigenous peoples of Cauca, applying the theoretical lines of “geographies of terror” and “alter-geopolitics” belonging to critical geopolitics.
Keywords: Critical geopolitics; geographies of terror; alter-geopolitics; Colombia; indigenous guard